Exploring the Wisdom of Prophet Sulaiman’s Story and the Hoopoe Through the Lens of Wahbah Zuhayli in al-Tafsir al-Munir - Simangunsong, Ali Abdurahman; Misnawati, Misnawati (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
The Qur'an uses stories as a medium to convey moral messages for the creation of a virtuous human community. Scholars, such as Wahbah Zuhaylī, interpret these stories and derive various lessons and wisdom from them. In his exegesis al-Munīr, Zuhaylī discusses the